Rodzinna piecza zastępcza nad dzieckiem – formy pomocy i wsparcia w codziennym funkcjonowaniu oraz w sytuacjach trudnych – kryzysowych - Matejek, Józefa (Kultura-Społeczeństwo-Edukacja, 2022)
Family foster care is a form of temporary care for children who, for various reasons, cannot grow up in a biological family. Foster families have a variety of tasks to fulfill, resulting not only from the current custody of the child, but also from the need for extensive compensation for the general developmental deficiencies of the child placed in it. The purpose of the article is to present the possibilities and forms of support directed to children residing in foster families who have experienced various difficult situations and crisis events in their biological families, as well as general assistance that can be obtained by foster families in which difficult crisis situations arise concerning daily functioning.